Cytogenetic Evidence for Sex Chromosomes and Karyotype Evolution in Anguimorphan Lizards - Augstenová, Barbora; Pensabene, Eleonora; Kratochvíl, Lukáš; Rovatsos, Michail (Cells, 2021)
Anguimorphan lizards are a morphologically variable group of squamate reptiles with a wide geographical distribution. In spite of their importance, they have been cytogenetically understudied. Here, we present the results of the cytogenetic examination of 23 species from five anguimorphan families (Anguidae, Helodermatidae, Shinisauridae, Varanidae and Xenosauridae). We applied both conventional (Giemsa staining and C-banding) and molecular cytogenetic methods (fluorescence in situ hybridization with probes for the telomeric motifs and rDNA loci, comparative genome hybridization), intending to describe the karyotypes of previously unstudied species, to uncover the sex determination mode, and to reveal the distribution of variability in cytogenetic characteristics among anguimorphan lizards. We documented that karyotypes are generally quite variable across anguimorphan lineages, with anguids being the most varying. However, the derived chromosome number of 2n = 40 exhibits a notable long-term evolutionary stasis in monitors. Differentiated ZZ/ZW sex chromosomes were documented in monitors and helodermatids, as well as in the anguids Abronia lythrochila, and preliminary also in Celestus warreni and Gerrhonotus liocephalus. Several other anguimorphan species have likely poorly differentiated sex chromosomes, which cannot be detected by the applied cytogenetic methods, although the presence of environmental sex determination cannot be excluded. In addition, we uncovered a rare case of spontaneous triploidy in a fully grown Varanus primordius.
Keywords: Sex Chromosomes; pohlavní chromozomy; fylogeneze; Metaphase; telomeres; Phylogeny; Telomere; ribozomální DNA; karyotyp; molekulární evoluce; Evolution, Molecular; rDNA; Lizards; ještěři; FISH; sex chromosomes; Animals; evolution; telomery; zvířata; metafáze; CGH; DNA, Ribosomal; cytogenetické vyšetření; karyotype; Cytogenetic Analysis; Karyotype